Preiskava bolezenskih proteomov z dvodimenzionalno gelsko elektroforezo in masno spektrometrijo - Kočevar, Nina (Medicinski razgledi, 2008)
A two-dimensional gel electrophoresis is one of the basic techniques of proteomics. It is used to separate proteins. As already hinted by the name, weare using the method to separate proteins in two dimensions. Firstly, they are separated during isoelectric focusing according to their isoelectric points and then according to their molecular weight during sodium dodecyl sulphate polyacrylamide gel electrophoresis - resulting in a gel with round spots of separated proteins. The method is usually used in combination with mass spectrometry and bioinformatics: the first one enables us to identify thedesired proteins (i. e. those with differential expression in compared samples), and the second one enables us to use different computer programer for determining the spots (proteins) with differential expression, as well as identifying them by using different databases. In this article we methodologically describe phases of proteome investigation, from sample preparation and two-dimensional gel electrophoresis to gel analysis with mass spectrometry and protein identification. We are showing the possibilities of using the method in biomedicine, with particular focus on our research of oncogenesis at gastric mucosa.
Keywords: Proteins; Zaporedje, analiza; Beljakovine; Electrophoresis, Gel, Two-Dimensional; Spectrum Analysis, Mass; Spektralna analiza masna; Sequence Analysis; Elektroforeza gelska, dvodimenzionalna; biomedicina; proteom; elektroforeza; masna spektrometrija